KHIDR’S IMAGE IN CLASSICAL AND MODERN LITERATURE AND FOLK ORAL TRADITION - Burieva Oliya Zayliyevna (Bright Mind Publishing, 2025)
This article analyzes the interpretation of the figure of Khidr (peace be upon him) in religious, philosophical, and literary sources based on the Qur’an and Islamic narratives. It highlights how the image of Khidr has been shaped in Uzbek classical and contemporary literature, as well as in folk oral tradition, and what ideological and aesthetic significance it carries.
Keywords: Khidr (peace be upon him), Qur’an, artistic image, symbol, classical literature, folk oral tradition.